Perkahwinan adat Rembau - Negeri Sembilan. Jabatan Kebudayaan, Kesenian & Warisan ([Seremban] : Jabatan Kebudayaan, Kesenian & Warisan, Negeri Sembilan, Kementerian Kebudayaan, Kesenian & Warisan, Malaysia, 2006)
Documentary on Malay marriage customs and rites in Rembau, Negeri Sembilan, Malaysia.
In Malay.
Keywords: Marriage customs and rites -- Malaysia -- Rembau (Negeri Sembilan); Minangkabau (Indonesian people) -- Marriage customs and rites -- Malaysia -- Rembau (Negeri Sembilan); Rembau (Negeri Sembilan) -- Social life and customs